Values of University Students: Implications for Human Education - Sánchez Hernández, Claudia María (Paradigma: Revista de Investigación Educativa, 2021)
The interest of the study was to understand how young students of the Universidad Pedagógica Nacional Francisco Morazán perceive the values they possess and the human formation they receive at the university. The ten types of value posed by Schwartz’s Theory (conformity, tradition, universalism, benevolence, security, self-direction, stimulation, hedonism, achievement, and power) were established from the qualitative approach as theoretical categories. Four focus groups were carried out, identifying sub-categories associated with each type of value. The results indicate that collective values are given greater importance than individual values. The meaning of human formation in the university is revealed. The challenge is posed for professors in their role as trainers,in this postmodern era, which makes training complex, ethical commitment is seen as something lasting and not temporary.